2005
DOI: 10.7861/clinmedicine.5-3-240
|View full text |Cite
|
Sign up to set email alerts
|

Migration of healthcare professionals: practical and ethical considerations

Abstract: -Recruitment of healthcare professionals from developing countries to the UK is escalating rapidly, and is severely damaging the fragile healthcare systems of the countries involved. This is happening in spite of the Code of Practice of the Department of Health, which, although voluntary, was supposed to restrict such migration; unfortunately it has not proved effective so far. Steps are now urgently required to reverse this trend, in order to prevent the total collapse of some overseas health services. The De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The complex problem of HCW shortage, its causes and driving forces, are interrelated and require a multifaceted approach 56 57…”
Section: Strategies To Address Hcw Shortagementioning
confidence: 99%
“…The complex problem of HCW shortage, its causes and driving forces, are interrelated and require a multifaceted approach 56 57…”
Section: Strategies To Address Hcw Shortagementioning
confidence: 99%
“…44 In short, the importation of thousands of physicians from overseas into the US physician labor force may help reduce the physician shortage in this country, but the drain on skilled health professionals in the countries from which they emigrated contributes to even more severe healthcare workforce shortages, perhaps to the point of healthcare system collapse in the near future. 45 Such a strategy is neither a practical, sustainable, nor ethical solution to the problem of the short-and longterm physician shortage in the United States.…”
Section: Physiciansmentioning
confidence: 99%
“…7,9,10 It is widely agreed that current shortages in the United States, Canada and United Kingdom have resulted from setting inappropriate targets for training positions in the 1990's. 3,9,11 It will take years, however, to rectify the consequences of these decisions. Until then, developing countries will continue to bleed trained professionals into the global work force market.…”
Section: Long-term Solutionsmentioning
confidence: 99%
“…Africa has more than 24% of the disease burden, 3% of the globe's health workers, and less than 1% of global financial health resources even when loans and grants are taken into account. D Although the ethics of this 'brain drain' has been deplored by many, 3,8,9,11 voluntary restraining measures have proved ineffective. 11 It has been suggested that receiving countries should at least be required to reimburse donor countries for the education cost of the professionals they receive, 8,13 but I am unaware that this ever occurs.…”
Section: Long-term Solutionsmentioning
confidence: 99%
See 1 more Smart Citation